Association between Knowledge and Practice of Breast Self-examination (BSE) for Raising Awareness in Women about Breast Cancer: A Literature Review - Miftalia Anugrah Putri, Deka (KnE Life Sciences, 2021)
Breast cancer (BC) is the most common type of cancers in women in many countries, ranking fifth in terms of cancer mortality among women. The problem is getting bigger because >70% of the patients of BC present at an advanced stage. There are many ways to prevent BC. Early examination or early detection is one of them, which helps in reducing the severity of BC. Several studies have shown that Breast Self-examination (BSE) is a simple, feasible way for the early detection of BC in lowand middle-income countries. There is evidence that women who correctly practice BSE on a monthly basis are more likely to detect a lump in the early stage of its development, and early diagnosis has been reported to influence early treatment. This review used a non-systematic method, sources were gathered using Google Scholar, Medline, Science Direct, and relevant articles published in English and Indonesian were accessed in full-text pdf format. Articles were analysed, extracted, synthesized and then the evidence was determined. All selected articles used a cross-sectional method with questionnaires as the instrument of data collection. The majority of study sample had unsatisfactory knowledge about BSE, and did not practice BSE frequently. The factors contributing to their unsatisfactory knowledge were: occupation, education, exposure to media information, access to medical personnel, and history of breast-related disease. Keywords: knowledge, practice, breast self-examination, breast cancer